Improving Understanding and Skills of MSME Financial Bookkeeping through Simple Accounting Training - Mela Novita Rizki; Irna Herliza Rizki (Outline Journal of Community Development, 2025)
The financial recording capability of small business actors remains limited due to the lack of understanding and skills in basic accounting practices. This service program was designed to address that problem by enhancing the knowledge and practical competence of micro and small entrepreneurs in implementing simple and structured financial bookkeeping. The purpose of this activity was to empower business owners to independently manage their financial records for better decision-making and business sustainability. The applied method in this activity was an educative and participatory approach, consisting of three stages: initial needs assessment through interviews and observations, implementation of interactive training and direct practice using real transaction cases, and evaluation using pre- and post-tests, observations, and interviews. The results showed a significant increase in participants’ abilities to manage cash records, prepare basic financial reports, and utilize spreadsheet tools effectively. Participants also showed behavioral changes in adopting routine bookkeeping and separating business finances from personal expenses. This program proved to be effective in building a new financial culture among participants, both in the short term and with potential long-term benefits. The activity concluded that targeted and practice-based training can significantly improve financial literacy and management among small-scale business owners.